The Effectiveness Of Social Media Marketing Activity (SMMA) In Higher Education (A Consumer Decision Model/CDM Approach) - Agus Sriyanto; Purwanto Purwanto; Zaenal Muttaqin (UNIVED Press, 2025)
This study aims to describe the effectiveness of social media marketing (SMMA) on Instagram in building prospective students' interest in enrolling at UIN Raden Mas Said Surakarta, using the Consumer Decision Model (CDM) approach. This study identifies the important role of social media in influencing brand recognition, trust, positive attitudes, and prospective students' intentions. Instagram has proven to be a strategic platform for delivering relevant information to the younger generation. The findings show that trust is the most influential mediating variable in shaping enrollment intentions. Consistent and quality content can increase prospective students' trust, while interactive elements and personalization strengthen positive impressions of the institution. This study emphasizes the importance of strong brand management on social media, where good brand recognition increases prospective students' trust and positive attitudes. In addition, content that displays achievements, alumni testimonials, and responsive interactions have proven effective in building a positive image. As an academic contribution, this study introduces the application of the CDM model in marketing, providing a new perspective on how social media influences positive attitudes and prospective students' intentions to enroll, especially in universities in Indonesia.